Individualisierung und mobile Dienste am Beispiel der Medienbranche Ansätze zum Schaffen von Kundenmehrwert - Kaspar, Christian Markus (Universitätsverlag Göttingen, 2006)
Christian Kaspar deals with the causes of the current economic crisis in the media industry and discusses opportunities for media companies to avert this crisis. Two options particularly are considered in more detail: the approaching of media products to individual desires of recipients on the basis of individualized systems on the one hand and the quick and location-independent distribution of contents through the mobile internet on the other. Kaspar makes point of two aims: First, it is examined whether and how far the strategies of individualization and distribution in the mobile internet are - compared with traditional media - able to provide additional benefit for customers. Second, conceptual issues in the context of realization of individual and mobile media products are raised and solutions are presented.